Representations of the natural world in Old English poetry - Neville, Jennifer, 1968- (Cambridge studies in Anglo-Saxon England ;, 1999)
This book examines descriptions of the natural world in a wide range of Old English poetry. Jennifer Neville describes the physical conditions experienced by the Anglo-Saxons - the animals, diseases, landscapes, seas and weather with which they had to contend. She argues that poetic descriptions of these elements were not a reflection of the existing physical conditions but a literary device used by Anglo-Saxons to define more important issues: the state of humanity, the creation and maintenance of society, the power of individuals, the relationship between God and creation, and the power of writing to control information.